P017 Non-antibody mediated pathogenic roles for synovial B cells in ACPA+ and ACPA- rheumatoid arthritis. (March 2019) - Floudas, A; Low, C; Biniecka, M; Veale, DJ; Fearon, U
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: RF and ACPA have been used extensively for the diagnosis of RA, however no clear mechanism of action towards disease pathogenesis and progression has been identified. Importantly, both seropositive and seronegative RA patients experience significant improvement in disease severity following B cell depletion. Therefore, we hypothesized that B cells have a central role in ACPA + and ACPA - RA irrespective of their capacity to produce auto-antibodies. Objectives: To characterize B and T cell populations, their recruitment to the inflamed joint, B cell cytokine production and CD4 + T cell polarization in RA synovial tissue biopsies and peripheral blood of ACPA +, ACPA - RA and arthralgia subjects. Methods: Synovial tissue biopsies from ACPA + and ACPA - RA and ACPA + arthralgia subjects, with paired blood/synovial fluid, were obtained through key-hole arthroscopy and were enzymatically digested. B cell invasion assays and B and CD4 + T cell in vitro stimulation were conducted under hypoxic conditions simulating the unique environment of the inflamed joint. Flow cytometric analysis was performed. Results: Significant accumulation, compared to peripheral blood, of pro-inflammatory B cells and pro-inflammatory cytokine-producing CD4 + T cells in the synovial tissue and fluid of RA patients, irrespective of ACPA status, as well as the synovial tissue of arthralgia subjects. SPICE analysis of peripheral blood B cells, for a panel of chemokine receptors, revealed a disease-specific expression pattern detected in RA and arthralgia subjects. Importantly, the tissue-invading B cells expressed CXCR3, with in vitro blockade of CXCR3 resulting in reduced B cell invasion in response to RA synovial tissue biopsy-conditioned media. Under the unique hypoxic conditions of the inflamed joint, RA patient but not healthy subject-derived B cells produce several pro-inflammatory cytokines including TNF-a and IL-6 and are capable of polarizing CD4 + T cells towards a pro-inflammatory phenotype. Conclusions: Accumulation of pro-inflammatory B cell subpopulations in the synovium of both ACPA + and ACPA - RA patients underlines a common, antibody-independent, contribution of B cells in synovial inflammation. Arthralgia early in disease, specific chemokine receptor expression and the accumulation of CXCR3 + B cells in the inflamed joint offers an opportunity for therapeutic intervention. Once in the hypoxic environment of the inflamed RA joint, B cells show altered activation, cytokine production and T cell polarization capacity that could prove important for understanding the role of B cells in disease pathogenesis of RA. Disclosure of Interest: None declared.